Sarcoidosis and Thyroid Autoimmunity - Fazzi, Piera; Fallahi, Poupak; Ferrari, Silvia Martina (Frontiers in Endocrinology, 2017)
Most of the studies have shown a higher risk for subclinical and clinical hypothyroidism, antithyroid autoantibodies [overall antithyroid peroxidase antibodies (TPOAb)], and in general thyroid autoimmunity, overall in the female gender in patients with sarcoidosis (S). A significantly higher prevalence of clinical hypothyroidism and Graves disease was also described in female S patients with respect to controls. Gallium-67 (Ga-67) scyntigraphy in S patients, in the case of thyroid uptake, suggests the presence of aggressive autoimmune thyroiditis and hypothyroidism. For this reason ultrasonography and thyroid function should be done in the case of Ga-67 thyroid uptake. In conclusion, thyroid function, TPOAb measurement, and ultrasonography should be done to assess the clinical profile in female S patients, and the ones at high risk (female individuals, with TPOAb positivity, and hypoechoic and small thyroid) should have periodically thyroid function evaluations and suitable treatments.